2008
DOI: 10.1007/bf03016088
|View full text |Cite
|
Sign up to set email alerts
|

Is operative delay associated with increased mortality of hip fracture patients? Systematic review, meta-analysis, and meta-regression

Abstract: Purpose: Mortality associated with hip fracture is high in elderly patients. Surgical repair within 24 hr after admission is recommended by The Royal College of Physicians' guidelines; however, the effect of operative delay on mortality remains controversial. The objective of this study was to determine whether operative delay increases mortality in elderly patients with hip fracture. Methods: Published English-language reports examining the effect of surgical delay on mortality in patients who underwent hip s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
338
1
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(383 citation statements)
references
References 26 publications
15
338
1
20
Order By: Relevance
“…This idea is further supported by studies showing, after adjusting for patient age, gender, and comorbidities, surgical delay greater than 1 day does not lead to an increase of mortality [21,24,30,47]. However, other studies have shown, even after adjusting for comorbidities, surgical delay greater than 48 hours led to an increase in 30-day and 1-year mortality rates [7,34,37,41,50]. Despite the conflicting evidence, we support early surgical intervention in healthy patients and those with minor physiologic abnormalities and attempt to delay surgery only in patients requiring physiologic stabilization or additional preoperative workup [46].…”
Section: Discussionmentioning
confidence: 91%
“…This idea is further supported by studies showing, after adjusting for patient age, gender, and comorbidities, surgical delay greater than 1 day does not lead to an increase of mortality [21,24,30,47]. However, other studies have shown, even after adjusting for comorbidities, surgical delay greater than 48 hours led to an increase in 30-day and 1-year mortality rates [7,34,37,41,50]. Despite the conflicting evidence, we support early surgical intervention in healthy patients and those with minor physiologic abnormalities and attempt to delay surgery only in patients requiring physiologic stabilization or additional preoperative workup [46].…”
Section: Discussionmentioning
confidence: 91%
“…Traditionally, surgery was postponed until patients had recovered from any acute illness and were deemed 'fit' for anaesthesia and surgery, resulting in pre-operative delay. There is now very strong evidence that delay from hospital admission to surgery increases mortality, lengthens hospital stay and delays functional recovery [67,68]. Delays normally relate to either organisational (51%) or medical (44%) problems, both of which are amenable to managed reduction [69].…”
Section: Pre-operative Optimisationmentioning
confidence: 99%
“…Numerous studies have reported the correlation between time to surgery and increased mortality [57, 71••, 72-76]. Shiga and colleagues' meta-analysis of 16 observational studies demonstrated increased mortality rates at 30 days and one year of 41 % and 32 % respectively when surgery was delayed more than 48 hours [73]. Other studies suggest similar mortality rates.…”
Section: Surgical Timingmentioning
confidence: 99%